Intensity and Prevalence of Helminth Parasites in Caranx leptolepisfrom Karangantu and Labuan - Agi Juniarso; Forcep Rio Indaryanto; Saifullah Saifullah (JURNAL PERIKANAN DAN KELAUTAN, 2016)
Helminth parasites cause ecologically, biologically and economically losses.Parasitic infections not only deadly for fish, but also decreased levels of fecundityand influenced fry development. The main commodities from Karangantu andLabuan fishing port are yellowstripe scad (Caranx leptolepis). The research aimsto identifies the intensity and prevalence of helminth parasites in yellowstripescad from Karangantu and Labuan fishing port. The experiment was conductedfrom May until June 2015. Measurement of fish biology and identification ofspecies of helminth parasites carried out in the Laboratory of AquacultureDepartment of Fisheries Faculty of Agriculture, University of Sultan AgengTirtayasa. The method used in this research is descriptive and sampling bycollecting various data of the sample studied. The results showed thatLechitocladium angustiovum and Lecitochirium sp. infected the yellowstripe scad(32% at gastric).